The Study of Knowledge, Attitude and Behavior of Nurses to Caring for the Elderly with Delirium after Cardiac Surgery - Naknonehun, Pornnapa; Jaipang, Chulaluk; Sanonoi, Nattaya; Piyawattanapong, Sirimart (Journal of The Royal Thai Army Nurses, 2020)
This descriptive research aimed to study 1) Knowledge about postoperative delirium, attitude towards postoperative delirium and behavior of nurses to caring for the elderly with postoperative delirium after cardiac surgery 2) The relationship between the knowledge and attitude on the behavior of nurses to caring for the elderly with delirium after cardiac surgery. The sample is 61 registered nurses in the cardiac and thoracic surgery ward. The research instrument consisted of a personal data record form, the Knowledge questionnaire about postoperative delirium, the Attitude questionnaire towards postoperative delirium, and the Behavior questionnaire of nurses to caring for the elderly with delirium after cardiac surgery. The reliability of the instruments was .80, .87, and .94 respectively. The results showed that the mean score of knowledge about postoperative delirium was 16.37 from 20 points (S.D. = 2.77). The mean score of attitude towards postoperative delirium was 3.62 from 5 points (S.D. = 0.49). The mean score of the behavior of nurses to caring for the elderly with delirium after cardiac surgery 3.99 from 5 points (S.D. = 0.57). The knowledge and attitude did not correlate with the behavior of nurses to caring for the elderly with postoperative delirium after cardiac surgery (p> .05).